Benefits of self-selected projects from students' workplace as a pedagogical tool in graduate operations management classes. (2015) - Jin, Alan; Wu, Lifang; Cunningham, Margaret; Chinta, Ravi
Project-based pedagogies are well recognised and widely adopted in business education. In this paper we present lessons from a project-based pedagogy specifically designed for Master of Business Administration (MBA) students: self-selected operations projects from their workplaces. We introduced this approach in two sections of our core MBA Operations Management course during the Spring 2014 semester, and then interviewed thirty-seven students to discover students' perceptions of the benefits of this pedagogy. Our analysis revealed that, from MBA students' perspective, self-selected projects from students' workplaces provided significant benefits to the students' workplace performance, professional and career development, project management experience, and course material learning. We conclude with the limitations of the study, implications for instructors, and suggestions for future research.